A Reform Dilemma in Polarized Democracies - Hans Gersbach; Oriol Tejada (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
We study the feasibility and efficiency of policy reforms in polarized democracies. We develop a simple election model where (i) reforms are costly for voters and politicians and these costs increase with the extent of policy change, and (ii) politicians differ in their ability to carry out reforms efficiently. We identify a so-called Reform Dilemma, which manifests itself in two variants. From a static perspective, low-reform-ability politicians may be elected, who impose high costs on citizens for each reform step. From a dynamic perspective, incumbents may choose socially undesirable policies to align the social need for reform with their own reform ability and are thus re-elected regardless of their reform ability. In general, both manifestations of the Reform Dilemma are more pronounced when political parties' positions are polarized. Furthermore, the existence of the Reform Dilemma is independent of the exact point in time when the abilities of candidates reveal themselves and become common knowledge.
Keywords: D72; D82; 330; Elections; democracy; costs of reform; political polarization; Politische Reform; Demokratie; Soziale Kosten; Ideologie; Politische Einstellung; Neue politische Ökonomie; Entscheidungstheorie